Life After Losing an Adult Child to a Drug Overdose: A Kawa Perspective - Aaron Weis; Julie D. Kugel; Heather Javaherian-Dysinger; Jessica Nicole De Brun (Scholarworks @ WMU, 2019)
Background: Limited research is available to occupational therapy practitioners focusing on parents' abilities to cope with the loss of an adult child to a drug overdose. We examined the unique experiences of grieving parents from a Kawa model perspective to identify potential implications for occupational therapy. Methods: We used a qualitative approach in which 11 participants completed Kawa drawings and participated in semistructured interviews. Results: Following a Kawa model analysis themes emerged: volatile nature of flow, support from inner circle and connection with outer circle, lonely islands, personal attributes of positivity and economics, and enhancing my river's flow. Conclusion: The loss of an adult child to a drug overdose presents health care professionals with a unique set of grieving circumstances, including changes in life roles and abilities to participate in occupations, which can be challenging to address. As a result, this study suggests the Kawa model is an effective assessment tool that should be considered for use when working with those grieving the loss of a child to a drug overdose.